“WAGGING THE DOG”: FEIGNING CRISIS IN U.S. ANTI-MIGRATION NARRATIVES TO CREATE CRISIS - Duffy, Maureen (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2019)
Anti-migration narratives are sweeping around the world, often accompanied by support for racist ideologies. The narratives usually involve some false claim that those seeking to enter the country are presumptively dangerous. Such narratives are obviously not new, but they are arguably being presented in evolving ways and having evolving, and deeply troubling, practical and legal effects. In the U.S., migrants being held in horrific “camp” conditions represent just the latest in a series of anti-migrant measures, each arguably worse than the last. This phenomenon is not limited to the U.S., but that example provides a strong vehicle for demonstrating this larger transnational trend. This article argues that harmful anti-migrant narratives are having significant, adverse effects on human rights and foundational legal norms.